Development of Solar Educational Training Kit - Ranjit, S.S.S.; Anas, S.A.; Subramaniam, S.K.; Tan , CheeFai; S.H., Chuah (2012)
The ability of utilize free resources of energy to generate electricity is one of the major tasks for environmentally research engineers. Numerous researches have been conducted to convert sunlight to direct current through Photovoltaic (PV) system. Nowadays PV research has become a popular study and has gained attention of many engineers and researchers due to free application, improving efficiency and high reliable energy source availability and is predicted to grow in years to come. With understanding of the aforementioned importance, PV systems aim to satisfy the growing demand for sustainable energy. This paper proposes a model of a real time grid assisted from low power direct current to high power alternating current as a solar educational training kit for an early education process to understand about the sustainability of energy conversion process. Integrating the switching concept, grid connection will only be switched on if the stored energy in the battery is insufficient to energize or supply the training kit. Programmable Integrated Circuit (PIC) is integrated into the educational training kit to enable it to display and indicates the battery voltage level as it also take part in switching between the battery and grid. In the nutshell, a simple and user friendly measurement training kit is intentionally designed for user’s handwork purposes.